PENGEMBANGAN YAYASAN PERGURUAN TINGGI SWASTA MEMBENTUK BADAN LAYANAN KEGIATAN USAHA - Nurpratama, Meddy; Yudianto, Agus; Firdaus, Taufansyah (Universitas Wiralodra, 2024)
The foundation law governing the establishment of Private Universities (PTS) emphasizes an orientation towards educational development rather than a profit orientation. The Foundation acts as the owner and manager of PTS, with a non-profit focus. Sustainability of PTS requires financial resources such as student tuition fees, grant funds, and collaboration. This statement highlights that universities not only function as centers of research, science and community service, but also as corporate entities that are active in producing knowledge. It is important for universities to compete, adapt, and have sensing capabilities in order to ensure survival amidst ever-changing environmental dynamics. The competition experienced by profit companies includes competition in the areas of price, quality and service. Universities as non-profit entities are also dealing with this. Management with adaptive capability resources, all of which require management knowledge and skills, namely higher education management.